2020
DOI: 10.1038/s41598-020-59569-0
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of semiochemical based push-pull strategy for population suppression of ambrosia beetle vectors of laurel wilt disease in avocado

Abstract: Ambrosia beetles (Coleoptera: Curculionidae: Scolytinae and Platypodinae) bore into tree xylem to complete their life cycle, feeding on symbiotic fungi. Ambrosia beetles are a threat to avocado where they have been found to vector a symbiotic fungus, Raffaelea lauricola, the causal agent of the laurel wilt disease. We assessed the repellency of methyl salicylate and verbenone to two putative laurel wilt vectors in avocado, Xyleborus volvulus (Fabricius) and Xyleborus bispinatus (Eichhoff), under laboratory con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 44 publications
(32 reference statements)
0
17
0
1
Order By: Relevance
“…As a consequence, alternative methods of aphid management are in high demand. One of the routes explored is the manipulation of aphid behavior so the insect is either disoriented or discouraged from feeding [11][12][13][14]. This is often achieved by the use of antifeedants or attractants, especially in the 'push-pull' strategies [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence, alternative methods of aphid management are in high demand. One of the routes explored is the manipulation of aphid behavior so the insect is either disoriented or discouraged from feeding [11][12][13][14]. This is often achieved by the use of antifeedants or attractants, especially in the 'push-pull' strategies [15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Addesso et al (2019) did not find ethanol-injected trap trees reduced attacks on adjacent, less attractive trees; varying densities of perimeter ethanolbaited traps also failed to protect ethanol-injected trap trees. However, Rivera et al (2020) observed a significant reduction in Xyleborus spp. ambrosia beetle captures (vectors of laurel wilt [Raffaelea lauricola T. C.…”
Section: Push-pull Strategiesmentioning
confidence: 85%
“…This management strategy, known as push-pull, manipulates the behavior of insects by combining the two forces: (1) a repellent to 'push' them away from the cultivated host and (2) an attractant to 'pull' them into a trap crop or artificial trap (Cook et al 2007). However, efforts to use ethanol lures or trap trees (i.e., ethanol-injected or flood-stressed plants) as a 'pull' attractant and synthetic repellents as a 'push' component has had inconsistent results (Ranger et al 2013b;Addesso et al 2019;Werle et al 2019;Rivera et al 2020).…”
Section: Push-pull Strategiesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, a push-pull strategy using ethanol traps and verbenone as attractants and repellents, respectively, failed to reduce non-native ambrosia beetle attacks on potted dogwoods [ 64 ]. In avocado, where R. lauricola is likely transmitted by beetles other than X. glabratus [ 65 ], a push-pull strategy using ethanol (that attracts most beetles found in avocado groves) and verbenone showed promising results [ 66 ]: the addition of attractive lures had a significant interaction with verbenone, and no ambrosia beetles were captured within the push-pull treatment on traps situated less than 1 m from the treated trees during the duration of the experiment (30 days).…”
Section: Moving To a Push-pull Systemmentioning
confidence: 99%